2021
DOI: 10.3390/ijms22031402
|View full text |Cite
|
Sign up to set email alerts
|

HPV Meets APOBEC: New Players in Head and Neck Cancer

Abstract: Besides smoking and alcohol, human papillomavirus (HPV) is a factor promoting head and neck squamous cell carcinoma (HNSCC). In some human tumors, including HNSCC, a number of mutations are caused by aberrantly activated DNA-modifying enzymes, such as the apolipoprotein B mRNA editing enzyme catalytic polypeptide-like (APOBEC) family of cytidine deaminases. As the enzymatic activity of APOBEC proteins contributes to the innate immune response to viruses, including HPV, the role of APOBEC proteins in HPV-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 102 publications
3
20
0
Order By: Relevance
“…The APOBEC family has been shown to induce tumor mutations by aberrant DNA editing mechanisms ( 49 ). Infection with high-risk HPV, which is one of the pathogenic factors in the oral and maxillofacial regions, leads to increased APOBEC family activity ( 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…The APOBEC family has been shown to induce tumor mutations by aberrant DNA editing mechanisms ( 49 ). Infection with high-risk HPV, which is one of the pathogenic factors in the oral and maxillofacial regions, leads to increased APOBEC family activity ( 50 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…HNSCC is usually associated with exposure to tobacco-derived carcinogens, excessive alcohol consumption, or both. Tumors appearing in the oropharynx are increasingly related to human papillomavirus (HPV) carcinogenic strains, mainly HPV-16, and to a lesser extent HPV-18 and other strains of infection ( Riva et al, 2021 ). In current treatment methods, only about 50% of HNSCC patients survive for more than 5 years.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of homologous recombination [ 75 ] and replication stress [ 80 ] have been linked to HPV integration and pathogenicity. Work from our group and others have demonstrated that APOBEC plays a key role in HPV-mediated carcinogenesis in the oropharynx [ 81 ], and increased expression and activity of APOBEC3B and APOBEC3A, respectively, have been linked to direct actions of HPV oncoproteins E6 and E7 [ 82 ]. APOBEC3s have been associated with genomic instability across multiple cancer types [ 83 ].…”
Section: Discussionmentioning
confidence: 99%